2003
DOI: 10.1136/qhc.12.6.405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the culture of safety: survey of clinicians and managers in an academic medical center

Abstract: Background: Despite the emphasis on patient safety in health care, few organizations have evaluated the extent to which safety is a strategic priority or their culture supports patient safety. In response to the Institute of Medicine's report and to an organizational commitment to patient safety, we conducted a systematic assessment of safety at the Johns Hopkins Hospital (JHH) and, from this, developed a strategic plan to improve safety. The specific aims of this study were to evaluate the extent to which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
154
2
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(176 citation statements)
references
References 11 publications
10
154
2
10
Order By: Relevance
“…This assumption is supported by earlier findings [58], where the staff with distance to patients and less education scored lowest for patient safety culture. Earlier research on perceptions of patient safety culture also show inconsistencies between RNs and physicians, where RNs scored higher than physicians for most questions [59]. In Haugen et al [58], variations were reported where nurse anesthetists scored higher than surgeon physicians both in outcome variables as well as for unit level dimensions.…”
Section: Discussion Of Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This assumption is supported by earlier findings [58], where the staff with distance to patients and less education scored lowest for patient safety culture. Earlier research on perceptions of patient safety culture also show inconsistencies between RNs and physicians, where RNs scored higher than physicians for most questions [59]. In Haugen et al [58], variations were reported where nurse anesthetists scored higher than surgeon physicians both in outcome variables as well as for unit level dimensions.…”
Section: Discussion Of Resultsmentioning
confidence: 93%
“…These results show that physicians, administrators and nurses considered patient safety as a nurse responsibility, yet only 8% of the physicians consider nurses as part of the decision-making team [60]. When managers aim at unifying views like the previously mentioned in order to improve patient safety, they need to be visible to front line staff [59] and bridge the professional boundaries [61]. Professionals from different disciplines must also cooperate [62] in order to make patient safety a responsibility for all health care staff, regardless of profession.…”
Section: Discussion Of Resultsmentioning
confidence: 93%
“…Por otra parte, en todos los estudios consultados, el personal percibe que los supervisores tienen un mayor compromiso con la seguridad que los gestores, lo que pone de manifiesto la necesidad de mostrar una actitud más proactiva por parte de la gerencia en temas relacionados con la seguridad del paciente [19][20][21][22][23][24][25] . En general, la percepción de seguridad de 2015 fue inferior a la obtenida en 2013, aunque el grado de seguridad percibida se mantuvo en 7,5.…”
Section: Discussionunclassified
“…El estilo de liderazgo, la personalidad y las actitudes de los directivos, pueden influir en las percepciones de los profesionales y en sus comportamientos y por tanto, tener importantes consecuencias para la seguridad del paciente 25 . La cultura organizacional es difícil de cambiar.…”
Section: Discussionunclassified
“…There is little evidence supporting links between organisational factors, medical errors and patient safety, 31 yet a number of instruments to measure safety culture or climate in health care have been developed. [32][33][34][35][36][37] A typical instrument is the Agency for Healthcare Research and Quality patient safety culture survey. 38 It measures concepts including: communication openness; feedback and communication about error; frequency of events reported; handoffs and transitions; management support for patient safety; non-punitive response to error; organisational learning/continuous improvement; overall perceptions of patient safety; staffing; supervisor/manager expectation and actions promoting safety; teamwork across units and within units.…”
Section: Safety Culture -A Research Measure That Doesn't Include the mentioning
confidence: 99%